The Religiosity Values in the Novel of the Split Moon in America Sky and its Relevance toward the Character Education Values - Wiryareja, Sutarman Tarman; Aman Santoso, Adina Pamungkas (ISTAWA, 2022)
This study aims to examine in depth the values of religiosity in the novel â€œBulan Terbelah di Langit di Amerikaâ€ Â (BTDLA) and its Â values of moral/character education contained of the novel.The method used in this research is a qualitative method with a literature review approach. This research is a library research, with the primary data source is the novel BTDLA by Hanum Salsabila Rais & Rangga Almahendra, and the secondary data sources are books, articles relevant to religious values, and research journals related to the novel. The data was collected by using literary research techniques. The technique used in this study was critical reading and content analysis.The results of this study indicate that there are religious values in the BTDLA novel and its relevance to the values of character education (morals), namely: (1) there is a good relationship between humans and God, humans with humans, humans with the environment, and society; (2) the relationship between humans and God is good and also depends on how humans treat other humans; (3) Learn about the values of caring for others, respecting differences, and remaining peaceful and prosperous without any debate and upholding religious tolerance, without tarnishing one's own beliefs or those of others.Â Â